Conformational and structural stability of n and 2-propylthiols: a revisit. Issue 17 (1st April 2022) - Tripathi, Manish Kumar; Ramanathan, Venkatnarayan
Abstract : C–C and C–S bond rotations give four minima for nP molecules. Computational predictions reinforced by ESPM, MCA, NBO, FMO and NCI analyses excellently matched with experimental results. Abstract : The conformational and structural stability of n -propanethiol (nP) is revisited owing to the prevailing ambiguity in the literature reported hitherto, and the rationale for 2-propanethiol's (2P) most stable conformers is analyzed. Based on the rotation around the C–C and C–S bonds, four conformers for nP and two conformers for 2-propanethiol (2P) were found to have the lowest energies at the CCSD/cc-pVDZ level of theory. The two conformers of 2P are anti (T), and gauche (G), and those of nP are T–G, G–G, T–T, and G–T. Rotational barriers, geometrical parameters, fundamental vibrational modes, and energy parameters reported herein agree exceedingly well with the reported experimental values for nP and 2P molecules. Furthermore, natural bond orbital (NBO), frontier molecular orbital (FMO), Mulliken charge (MC), electrostatic potential charge (ESP), and vibrational mode analyses were carried out to get a better understanding of both the thiols.